The Evolution of Match Running Performance in the Top Two Spanish Soccer Leagues: A Comparative Four-Season Study - Tomás García-Calvo; David Lobo-Triviño; Javier Raya-González; Roberto López del Campo; Ricardo Resta; Eduard Pons; José Carlos Ponce-Bordón (Journal of Functional Morphology and Kinesiology)
Objectives: This study uniquely examines the evolution of match running performance in official matches over four consecutive seasons (2019/2020–2022/23) within Spain’s top two professional soccer leagues (LaLiga). By analyzing differences between competitive league standards (First Division vs. Second Division), this research provides critical insights into how competition levels influence physical performance trends over time. Methods: A total of 6784 match observations were recorded from 95 teams competing in the First and Second Divisions (LaLiga). Performance metrics included total distance (TD), high-speed running (HSR, >21 km·h−1), very high-speed running (VHSR, 21.1–24 km·h−1), sprint distance (Sprint, >24 km·h−1), the number of HSR efforts (Nº. Sprints > 21 km·h−1), and sprint efforts (Nº. Sprints > 24 km·h−1), all analyzed using a computerized tracking system (TRACAB, ChyronHego, New York, NY, USA). Results: The primary findings indicated significantly higher match running performance in First Division matches compared to Second Division matches across all variables (p < 0.001). Furthermore, match running performance significantly increased over the four seasons in both leagues, with notably higher values during the 2021/22 and 2022/23 seasons for all physical performance metrics (p < 0.001). Conclusions: This study contributes to understanding the temporal evolution of soccer match performance across competition levels. The findings emphasize the importance of periodic performance monitoring and adapting training loads increasing high-intensity distances to align with escalating physical demands in modern soccer, offering valuable guidance for coaches and performance analysts.